Chemical Symmetry Breaking - Tamura, Rui (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book entitled "Chemical Symmetry Breaking" is a collective volume of state-of-the-art reports on unique nonlinear chemical and physical symmetry-breaking phenomena that were experimentally observed upon a thermally or photochemically induced phase transition in various organic condensed phases, such as metastable liquid crystals, crystals, amorphous solids, and colloidal polymer materials, only under nonequilibrium conditions. Each author summarizes the introductory section in simple terms but in detail for beginners in this field. We wish that many readers familiarize themselves with the general concepts and features of nonlinear and nonequilibrium (or out of equilibrium) complexity theory, which govern a variety of unique dynamic behaviors observed in chemistry, physics, life science and other fields, so that they may discover novel symmetry-breaking phenomena in their own research areas.